Electronic-grade high-purity TiO2 powder and preparation method thereof
Purification of industrial titanium liquid through a solid-phase column filled with modified diatomaceous earth solves the problem of removing impurity ions in industrial titanium liquid, significantly improves the purity and performance of TiO2 powder, and meets the raw material needs of high-end electronic products.
Patent Information
- Application Number
- CN202411848479.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is difficult to effectively remove impurities and ions from industrial titanium liquids, resulting in low purity and quality of TiO2 products, which cannot meet the needs of high-end fields such as electronics, optical and environmentally friendly materials.
The industrial titanium liquid was initially purified by a solid-phase column filled with modified diatomaceous earth. Through the thiolation and functional modification of modified diatomaceous earth, efficient adsorption and removal of metal ions such as Fe, Al, V, Cr and anions such as SO42- are achieved.
It significantly improves the purity and performance of TiO2 powder, meets the strict requirements of high-purity TiO2 in the electronics industry, and improves the crystallinity and controllability of the product's physical and chemical properties.
Smart Images

Figure CN119683677A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium dioxide, and in particular to electronic grade high-purity TiO2 powder and a preparation method thereof. Background Art
[0002] Titanium dioxide (TiO2) is an important inorganic compound that is widely used in various fields due to its excellent physical and chemical properties. As a white pigment, TiO2 has a high refractive index, excellent hiding power and tinting power, as well as good chemical stability and weather resistance.
[0003] The main application areas of TiO2 include the coating industry, plastic industry, paper industry, cosmetic industry, food industry, environmental protection field and electronic industry. In the coating industry, TiO2 is used as a white pigment in architectural coatings and automotive coatings; in the plastic industry, TiO2 is used as a plastic whitening agent and colorant; in the paper industry, TiO2 can improve the whiteness and opacity of paper; in the cosmetic industry, TiO2 is used in products such as sunscreen and foundation; in the food industry, TiO2 is used as food additive E171; in the environmental protection field, TiO2 is used for photocatalytic degradation of organic pollutants; in the electronic industry, TiO2 is used to produce electronic components such as capacitors and varistors.
[0004] In terms of crystal structure, TiO2 has three main crystal forms: anatase, rutile and brookite. Among them, anatase and rutile are the most widely used in industry. Rutile TiO2 has a higher refractive index and hiding power, and is mainly used in high-end coatings; while anatase TiO2 is more suitable for plastics and interior coatings.
[0005] At present, the production of TiO2 in my country mainly adopts the sulfuric acid process, in which industrial titanium liquid is an important intermediate product. Industrial titanium liquid is usually obtained by acidification, clarification, and concentration of titanium ore or titanium slag, and its concentration is generally between 140 and 190 g / L. However, in addition to the required titanium ions, this industrial titanium liquid also contains a large amount of impurity ions, such as SO4 2- , Fe, Al, V, Cr, Mn, etc. The presence of these impurity ions will have a serious impact on the quality of the final TiO2 product, including affecting the crystal transformation and grain growth of TiO2, generating lattice defects, reducing product purity, affecting product color, and affecting product performance.
[0006] As the application of TiO2 in high-end fields such as electronics, optics and environmental protection materials continues to expand, the requirements for its purity and performance are becoming higher and higher. Especially in the production of electronic grade TiO2, the control of impurities becomes particularly critical. High-purity TiO2 can significantly improve the performance and stability of electronic components.
[0007] Therefore, how to effectively remove impurity ions in industrial titanium liquid and improve the purity and quality of TiO2 is an important technical problem faced by the titanium dioxide industry. Existing treatment methods often have problems such as low efficiency, high cost, and secondary pollution, and it is difficult to meet the needs of large-scale industrial production. The development of an efficient, economical, and environmentally friendly industrial titanium liquid purification method has important practical significance for improving the quality of TiO2 products, reducing production costs, and enhancing product competitiveness. The present invention aims to solve the above problems and provide a new method for producing high-purity TiO2 using industrial titanium liquid, focusing on solving the problem of removing impurity ions in industrial titanium liquid to meet the growing market demand for high-quality TiO2. Summary of the invention
[0008] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide an electronic grade high-purity TiO2 powder and a preparation method thereof, and a solid phase column filled with modified diatomaceous earth is used to preliminarily purify the industrial titanium liquid, thereby effectively removing most of the impurity ions and significantly improving the purity of the raw materials. The finally obtained electronic grade high-purity TiO2 powder has high purity and excellent performance, and meets the strict requirements of the electronics industry for high-purity TiO2.
[0009] In order to achieve the above object, the present invention adopts the following technical solution:
[0010] A method for preparing electronic grade high-purity TiO2 powder comprises the following steps:
[0011] (1) adding industrial titanium liquid to a solid phase column and filtering to obtain a filtrate;
[0012] (2) adding the filtrate into a reaction kettle, sealing the reaction kettle, cooling the product, filtering to obtain a filter cake, washing and drying the filter cake to obtain hydrothermal metatitanic acid;
[0013] (3) Mixing hydrothermal titanic acid and NaOH solution to form a slurry, adjusting the pH, stirring at room temperature, filtering, washing, and drying the product to obtain desulfurized titanic acid; calcining the desulfurized titanic acid, cooling, and grinding to obtain the electronic grade high-purity TiO2 powder.
[0014] Preferably, in step (1), positive pressure is used to make the industrial titanium liquid pass through the solid phase column, and the flow rate is controlled to be 1.2 to 1.5 mL / min.
[0015] Specifically, in step (1), the flow rate is controlled to be 1.2, 1.3, 1.4, or 1.5 mL / min.
[0016] Preferably, in step (1), the total titanium concentration in the industrial titanium liquid is 140 to 190 g / L.
[0017] Specifically, in step (1), the total titanium concentration in the industrial titanium liquid can be 140, 150, 160, 170, 180, or 190 g / L.
[0018] Preferably, in step (2), the sealed reaction conditions are hydrothermal reaction at 110-160° C. and 0.2-1 MPa for 1-12 h.
[0019] Specifically, in step (2), the sealed reaction temperature can be 110, 120, 130, 140, 150, or 160° C., the reaction pressure can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1 MPa, and the reaction time can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 h.
[0020] Preferably, in step (3), the concentration of NaOH solution is 0.5-5wt%, and the pH is adjusted to 10-14; the stirring conditions at room temperature are stirring at 400-800r / min for 30-120min, the drying conditions are drying at 100-110°C for 1-3h; and the calcination conditions are calcining in a muffle furnace at 500-1000°C for 2-5h.
[0021] Specifically, in step (3), the pH can be adjusted to 10, 11, 12, 13, or 14; the stirring rate can be 400, 500, 600, 700, or 800 r / min; and the stirring time can be 30, 40, 50, 60, 70, 80, 90, 100, 110, or 120 min.
[0022] Preferably, in step (1), the solid phase column is filled with modified diatomaceous earth, and the preparation method of the modified diatomaceous earth comprises the following steps:
[0023] a. calcining diatomite in a muffle furnace, adding it to anhydrous ethanol after cooling, slowly adding KH580 dropwise under stirring, adjusting the pH, stirring the reaction, filtering the product, washing with alcohol, and drying it to obtain thiolated diatomite;
[0024] Activation and thiolation of diatomite: Diatomite is activated at high temperature to increase the surface active silanol groups. The activated diatomite reacts with a silane coupling agent containing a thiol group in an organic solvent. The silanization reaction is promoted by adjusting the pH value and controlling the reaction temperature: Si-OH (diatomite surface) + R-Si(OR')3 → Si-O-Si-R + 3R'OH, where R contains a thiol (-SH) functional group. This process introduces thiol groups on the surface of diatomite to form thiolated diatomite.
[0025] Preferably, in step a, the calcination conditions are calcination at 400-600° C. for 30-60 min; the usage ratio of diatomaceous earth, anhydrous ethanol and KH580 is 10 g:40-60 mL:0.5-3 g; the pH is adjusted to 5-6; and the stirring reaction conditions are stirring the reaction at 40-55° C. for 6-10 h.
[0026] Specifically, in step a, the calcination temperature can be 400, 450, 500, 550, 600°C, and the calcination time can be 30, 40, 50, 60 min; the pH can be adjusted to 5, 5.5, 6; the stirring reaction temperature can be 40, 45, 50, 55°C, and the stirring reaction time can be 6, 7, 8, 9, 10 h.
[0027] b. Disperse the thiolated diatomite in anhydrous ethanol, then dropwise add rose red ammonium tricarboxylate, adjust the pH, add 2,2-dimethoxy-2-phenylacetophenone, introduce nitrogen to expel the air, irradiate with ultraviolet light under a nitrogen atmosphere, stir to react, centrifuge the product, wash with alcohol, and dry to obtain the modified diatomite.
[0028] Functional modification of thiolated diatomite: thiolated diatomite and ammonium tricarboxylate were mixed in an organic solvent, a photoinitiator was added, the pH value was adjusted, and the photoreaction was carried out under the protection of an inert gas. This thiol-ene click reaction achieved functional modification of the diatomite surface under mild conditions.
[0029] Preferably, in step b, the usage ratio of thiolated diatomaceous earth, anhydrous ethanol, rose red ammonium tricarboxylate, and 2,2-dimethoxy-2-phenylacetophenone is 10 g: 40-60 mL: 0.5-2 g: 0.01-0.05 g.
[0030] Preferably, in step b, the pH is adjusted to 7.5-8.5; and the stirring reaction conditions are gentle stirring reaction at 25-40° C. for 1-4 hours.
[0031] Specifically, in step b, the pH can be adjusted to 7.5, 8, or 8.5; the stirring reaction temperature can be 25, 30, 35, or 40° C.; and the stirring reaction time can be 1, 2, 3, or 4 h.
[0032] The present invention also claims protection for an electronic grade high-purity TiO2 powder prepared by the preparation method.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The present invention provides a method for preparing electronic grade high-purity TiO2 powder, which uses a solid phase column filled with modified diatomite to preliminarily purify industrial titanium liquid. This key step uses modified diatomite to purify metal ions such as Fe, Al, V, Cr and SO4 2-The excellent selective adsorption capacity of anions efficiently removes most of the impurities in industrial titanium liquid and significantly improves the purity of raw materials. This not only creates favorable conditions for subsequent processes, but also reduces the burden of subsequent steps, improves the efficiency of the entire production process and the consistency of product quality. It ensures that the final product has high purity, good crystallinity and controllable physical and chemical properties, meets the strict requirements of electronic grade TiO2, and provides high-quality raw material support for high-end electronic products.
[0035] 2. The present invention provides a method for preparing modified diatomite. First, after diatomite is activated by high-temperature calcination, it is reacted with KH580 (γ-mercaptopropyltrimethoxysilane) to introduce a thiol group. This step forms a Si-O-Si bond on the surface of diatomite through a silanization reaction, and at the same time introduces a thiol (-SH) functional group to obtain thiolated diatomite. Subsequently, the thiolated diatomite is photo-reacted with 5-[(3-carboxyl-4-hydroxyphenyl) (3-carboxyl-4-oxo-2,5-cyclohexadiene-1-ylidene) methyl]-2-hydroxybenzoic acid triammonium salt (rose red tricarboxylate ammonium) in the presence of a photoinitiator 2,2-dimethoxy-2-phenylacetophenone. This step utilizes thiol-ene click chemistry. Under ultraviolet light irradiation, the photoinitiator generates free radicals, which trigger an addition reaction between the thiol group and the unsaturated bonds in the rose red tricarboxylate ammonium molecule, thereby achieving surface functionalization modification and finally obtaining modified diatomite.
[0036] 3. The present invention provides a modified diatomite. First, diatomite itself has a large specific surface area and a unique porous structure. These characteristics are retained and further optimized during the modification process, providing an excellent carrier basis for subsequent functionalization, and significantly improving the adsorption capacity and adsorption rate of impurities. Secondly, the sulfur atoms introduced by thiolization have a large atomic radius and easy polarization characteristics, which can generate a negative electric field, effectively capture metal cations in industrial titanium liquid, form insoluble, chemically stable precipitates, and achieve preliminary impurity removal. Subsequently, the rose-red ammonium tricarboxylate molecules introduced on the surface provide a variety of active functional groups, mainly including carboxyl and hydroxyl groups, and further efficiently adsorb various impurity ions in industrial titanium liquid through mechanisms such as ion exchange, coordination and hydrogen bonding. The functional groups introduced by these two steps of modification can also produce synergistic effects: the thiol group provides a preliminary metal ion capture capability, while the carboxyl and hydroxyl groups further enhance the selective adsorption of polyvalent metal ions, forming a multi-level, efficient impurity removal system, thereby effectively reducing the amount of ferrous ions adsorbed on the surface of metatitanic acid, and significantly improving the purity of the final titanium dioxide product. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show schematic diagrams of certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 This is the SEM image of the electronic grade high-purity TiO2 powder prepared in Example 1. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0040] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.
[0041] Rose red ammonium tricarboxylate, that is, 5-[(3-carboxy-4-hydroxyphenyl)(3-carboxy-4-oxo-2,5-cyclohexadiene-1-ylidene)methyl]-2-hydroxybenzoic acid triammonium salt, CAS: 569-58-4, is a commonly used aluminum reagent, and its structural formula is as follows:
[0042]
[0043] A method for preparing electronic grade high-purity TiO2 powder comprises the following steps:
[0044] (1) 10 g of diatomaceous earth is calcined in a muffle furnace at 400-600° C. for 30-60 min, and after cooling, it is added to 40-60 mL of anhydrous ethanol, and 0.5-3 g of KH580 is slowly added dropwise under stirring, and the pH is adjusted to 5-6. The reaction is stirred at 40-55° C. for 6-10 h, and the product is filtered, washed with alcohol, and dried to obtain thiolated diatomaceous earth;
[0045] (2) dispersing 10 g of thiolated diatomite in 40-60 mL of anhydrous ethanol, then dropwise adding 0.5-2 g of rose red ammonium tricarboxylate, adjusting the pH to 7.5-8.5, adding 0.01-0.05 g of 2,2-dimethoxy-2-phenylacetophenone, passing nitrogen gas to expel the air, irradiating ultraviolet light under a nitrogen atmosphere, and reacting at 25-40° C. with gentle stirring for 1-4 h, centrifuging the product, washing with alcohol, and drying to obtain modified diatomite;
[0046] (3) adding the industrial titanium liquid into a solid phase column filled with modified diatomaceous earth, passing the industrial titanium liquid through the solid phase column under positive pressure, controlling the flow rate to be 1.2 to 1.5 mL / min, and filtering to obtain a filtrate;
[0047] (4) adding the filtrate to a reaction kettle, carrying out a hydrothermal reaction at 110-160° C. and 0.2-1 MPa for 1-12 h, cooling and filtering the product to obtain a filter cake, washing and drying the filter cake to obtain hydrothermal metatitanic acid;
[0048] (5) Mixing hydrothermal titanic acid with 0.5-5wt% NaOH solution to form a slurry, adjusting the pH to 10-14, stirring at room temperature at 400-800 r / min for 30-120 min, filtering the product, washing, and drying at 100-110°C for 1-3 h to obtain desulfurized titanic acid; calcining the desulfurized titanic acid in a muffle furnace at 500-1000°C for 2-5 h, cooling, and grinding to obtain the electronic grade high-purity TiO2 powder.
[0049] The present invention will be further described below through specific embodiments.
[0050] Example 1
[0051] A method for preparing electronic grade high-purity TiO2 powder comprises the following steps:
[0052] (1) 10 g of diatomaceous earth was calcined at 600° C. for 30 min in a muffle furnace, and after cooling, it was added to 50 mL of anhydrous ethanol, and 3 g of KH580 was slowly added dropwise under stirring, and the pH was adjusted to 5.5. The reaction was stirred at 55° C. for 6 h, and the product was filtered, washed with alcohol, and dried to obtain thiolated diatomaceous earth;
[0053] (2) 10 g of thiolated diatomite was dispersed in 50 mL of anhydrous ethanol, and then 2 g of rose red ammonium tricarboxylate was added dropwise, the pH was adjusted to 8, 0.05 g of 2,2-dimethoxy-2-phenylacetophenone was added, nitrogen was introduced to expel the air, ultraviolet light was irradiated under a nitrogen atmosphere, and the reaction was gently stirred at 40° C. for 1 h, the product was centrifuged, washed with alcohol, and dried to obtain modified diatomite;
[0054] (3) adding the industrial titanium liquid into a solid phase column filled with modified diatomaceous earth, passing the industrial titanium liquid through the solid phase column under positive pressure, controlling the flow rate to 1.4 mL / min, and filtering to obtain a filtrate;
[0055] (4) adding the filtrate to a reactor, carrying out a hydrothermal reaction at 140° C. and 0.6 MPa for 6 h, cooling and filtering the product to obtain a filter cake, washing and drying the filter cake to obtain hydrothermal metatitanic acid;
[0056] (5) Mixing hydrothermal titanic acid with 2.5 wt% NaOH solution to form a slurry, adjusting the pH to 12, stirring at room temperature for 60 min at 600 r / min, filtering the product, washing, and drying at 105° C. for 2 h to obtain desulfurized titanic acid; calcining the desulfurized titanic acid in a muffle furnace at 500° C. for 5 h, cooling, and grinding to obtain the electronic grade high-purity TiO2 powder.
[0057] Example 2
[0058] (1) 10 g of diatomaceous earth was calcined in a muffle furnace at 500° C. for 45 min, and after cooling, it was added to 50 mL of anhydrous ethanol, and 2.5 g of KH580 was slowly added dropwise under stirring, and the pH was adjusted to 5.5. The reaction was stirred at 50° C. for 7 h, and the product was filtered, washed with alcohol, and dried to obtain thiolated diatomaceous earth;
[0059] (2) 10 g of thiolated diatomite was dispersed in 50 mL of anhydrous ethanol, and then 1.5 g of rose red ammonium tricarboxylate was added dropwise, the pH was adjusted to 8, 0.04 g of 2,2-dimethoxy-2-phenylacetophenone was added, nitrogen was introduced to expel the air, ultraviolet light was irradiated under a nitrogen atmosphere, and the reaction was gently stirred at 35° C. for 2 h, the product was centrifuged, washed with alcohol, and dried to obtain modified diatomite;
[0060] (3) adding the industrial titanium liquid into a solid phase column filled with modified diatomaceous earth, passing the industrial titanium liquid through the solid phase column under positive pressure, controlling the flow rate to 1.4 mL / min, and filtering to obtain a filtrate;
[0061] (4) adding the filtrate to a reactor, carrying out a hydrothermal reaction at 140° C. and 0.6 MPa for 6 h, cooling and filtering the product to obtain a filter cake, washing and drying the filter cake to obtain hydrothermal metatitanic acid;
[0062] (5) Mixing hydrothermal titanic acid with 2.5 wt% NaOH solution to form a slurry, adjusting the pH to 12, stirring at room temperature for 60 min at 600 r / min, filtering the product, washing, and drying at 105° C. for 2 h to obtain desulfurized titanic acid; calcining the desulfurized titanic acid in a muffle furnace at 600° C. for 3 h, cooling, and grinding to obtain the electronic grade high-purity TiO2 powder.
[0063] Example 3
[0064] (1) 10 g of diatomaceous earth was calcined in a muffle furnace at 400° C. for 60 min, and after cooling, it was added to 50 mL of anhydrous ethanol, and 0.5 g of KH580 was slowly added dropwise under stirring, and the pH was adjusted to 5.5. The reaction was stirred at 40° C. for 10 h, and the product was filtered, washed with alcohol, and dried to obtain thiolated diatomaceous earth;
[0065] (2) 10 g of thiolated diatomite was dispersed in 50 mL of anhydrous ethanol, and then 0.5 g of rose red ammonium tricarboxylate was added dropwise, the pH was adjusted to 8, 0.01 g of 2,2-dimethoxy-2-phenylacetophenone was added, nitrogen was introduced to expel the air, ultraviolet light was irradiated under a nitrogen atmosphere, and the reaction was gently stirred at 25° C. for 4 h, the product was centrifuged, washed with alcohol, and dried to obtain modified diatomite;
[0066] (3) adding the industrial titanium liquid into a solid phase column filled with modified diatomaceous earth, passing the industrial titanium liquid through the solid phase column under positive pressure, controlling the flow rate to 1.4 mL / min, and filtering to obtain a filtrate;
[0067] (4) adding the filtrate into a reactor, carrying out a hydrothermal reaction at 140° C. and 0.6 MPa for 6 h, cooling and filtering the product to obtain a filter cake, washing and drying the filter cake to obtain hydrothermal metatitanic acid;
[0068] (5) Mixing hydrothermal titanic acid with 2.5 wt% NaOH solution to form a slurry, adjusting the pH to 12, stirring at room temperature for 60 min at 600 r / min, filtering the product, washing, and drying at 105° C. for 2 h to obtain desulfurized titanic acid; calcining the desulfurized titanic acid in a muffle furnace at 700° C. for 3 h, cooling, and grinding to obtain the electronic grade high-purity TiO2 powder.
[0069] Comparative Example 1
[0070] A method for preparing TiO2 powder comprises the following steps:
[0071] (1) 10 g of diatomaceous earth was calcined at 600° C. for 30 min in a muffle furnace, and after cooling, it was added to 50 mL of anhydrous ethanol, and 3 g of KH580 was slowly added dropwise under stirring, and the pH was adjusted to 5.5. The reaction was stirred at 55° C. for 6 h, and the product was filtered, washed with alcohol, and dried to obtain thiolated diatomaceous earth;
[0072] (2) adding the industrial titanium liquid into a solid phase column filled with thiolated diatomaceous earth, passing the industrial titanium liquid through the solid phase column under positive pressure, controlling the flow rate to be 1.4 mL / min, and filtering to obtain a filtrate;
[0073] (3) adding the filtrate into a reactor, carrying out a hydrothermal reaction at 140° C. and 0.6 MPa for 6 h, cooling and filtering the product to obtain a filter cake, washing and drying the filter cake to obtain hydrothermal metatitanic acid;
[0074] (4) Mixing hydrothermal titanic acid with 2.5 wt% NaOH solution to form a slurry, adjusting the pH to 12, stirring at room temperature for 60 min at 600 r / min, filtering the product, washing, and drying at 105° C. for 2 h to obtain desulfurized titanic acid; calcining the desulfurized titanic acid in a muffle furnace at 500° C. for 5 h, cooling, and grinding to obtain the TiO2 powder.
[0075] Comparative Example 2
[0076] A method for preparing TiO2 powder comprises the following steps:
[0077] (1) adding industrial titanium liquid into a solid phase column filled with diatomaceous earth, passing the industrial titanium liquid through the solid phase column under positive pressure, controlling the flow rate to be 1.4 mL / min, and filtering to obtain a filtrate;
[0078] (2) adding the filtrate into a reactor, carrying out a hydrothermal reaction at 140° C. and 0.6 MPa for 6 h, cooling and filtering the product to obtain a filter cake, washing and drying the filter cake to obtain hydrothermal metatitanic acid;
[0079] (3) Mixing hydrothermal titanic acid with 2.5 wt% NaOH solution to form a slurry, adjusting the pH to 12, stirring at room temperature for 60 min at 600 r / min, filtering the product, washing, and drying at 105° C. for 2 h to obtain desulfurized titanic acid; calcining the desulfurized titanic acid in a muffle furnace at 500° C. for 5 h, cooling, and grinding to obtain the TiO2 powder.
[0080] The purity of the TiO2 powders prepared in Examples 1 to 4 and Comparative Examples 1 to 2 was tested by X-ray fluorescence spectrometer (XRF). The specific data are shown in Table 1.
[0081] Table 1 TiO2 powder test results
[0082] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 <![CDATA[TiO2 content (%)]]> ≥99.9 ≥99.9 ≥99.9 99.4 98.7 Fe content (%) ≤0.0005 ≤0.0005 ≤0.0005 0.26 0.48 Cu content (%) ≤0.005 ≤0.005 ≤0.005 0.06 0.17 Al content (%) ≤0.0005 ≤0.0005 ≤0.0005 0.14 0.25 Cd content (%) ≤0.005 ≤0.005 ≤0.005 0.01 0.08 Ni content (%) ≤0.005 ≤0.005 ≤0.005 0.04 0.13 Zn content (%) ≤0.005 ≤0.005 ≤0.005 0.06 0.16 <![CDATA[D 50 (μm)]]> 0.9 1.2 1.7 1.4 2.1
[0083] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing electronic grade high-purity TiO2 powder, characterized in that: The steps include: (1) adding industrial titanium liquid to a solid phase column and filtering to obtain a filtrate; (2) adding the filtrate into a reaction kettle, sealing the reaction kettle, cooling the product, filtering to obtain a filter cake, washing and drying the filter cake to obtain hydrothermal metatitanic acid; (3) mixing hydrothermal metatitanic acid and NaOH solution to form a slurry, adjusting the pH, stirring at room temperature, filtering, washing, and drying the product to obtain desulfurized metatitanic acid; The desulfurized metatitanic acid is roasted, cooled and ground to obtain the electronic grade high-purity TiO2 powder.
2. The preparation method according to claim 1, characterized in that: In step (1), positive pressure is used to make the industrial titanium liquid pass through the solid phase column, and the flow rate is controlled to be 1.2 to 1.5 mL / min.
3. The preparation method according to claim 1, characterized in that: In step (1), the total titanium concentration in the industrial titanium liquid is 140-190 g / L.
4. The preparation method according to claim 1, characterized in that: In step (2), the sealed reaction conditions are hydrothermal reaction at 110-160° C. and 0.2-1 MPa for 1-12 hours.
5. The preparation method according to claim 1, characterized in that: In step (3), the concentration of NaOH solution is 0.5-5wt%, and the pH is adjusted to 10-14; the stirring condition at room temperature is stirring at 400-800r / min for 30-120min, the drying condition is drying at 100-110°C for 1-3h; and the calcination condition is calcining in a muffle furnace at 500-1000°C for 2-5h.
6. The preparation method according to claim 1, characterized in that: In step (1), the solid phase column is filled with modified diatomaceous earth, and the preparation method of the modified diatomaceous earth comprises the following steps: a. calcining diatomite in a muffle furnace, adding it to anhydrous ethanol after cooling, slowly adding KH580 dropwise under stirring, adjusting the pH, stirring the reaction, filtering the product, washing with alcohol, and drying it to obtain thiolated diatomite; b. Disperse the thiolated diatomite in anhydrous ethanol, then dropwise add rose red ammonium tricarboxylate, adjust the pH, add 2,2-dimethoxy-2-phenylacetophenone, introduce nitrogen to expel the air, irradiate with ultraviolet light under a nitrogen atmosphere, stir to react, centrifuge the product, wash with alcohol, and dry to obtain the modified diatomite.
7. The preparation method according to claim 6, characterized in that: In step a, the calcination condition is calcination at 400-600° C. for 30-60 min; the usage ratio of diatomaceous earth, anhydrous ethanol and KH580 is 10 g:40-60 mL:0.5-3 g; the pH is adjusted to 5-6; and the stirring reaction condition is stirring the reaction at 40-55° C. for 6-10 h.
8. The preparation method according to claim 6, characterized in that: In step b, the usage ratio of thiolated diatomaceous earth, anhydrous ethanol, rose red ammonium tricarboxylate, and 2,2-dimethoxy-2-phenylacetophenone is 10 g: 40-60 mL: 0.5-2 g: 0.01-0.05 g.
9. The preparation method according to claim 6, characterized in that: In step b, the pH is adjusted to 7.5-8.5; the stirring reaction conditions are gentle stirring reaction at 25-40° C. for 1-4 hours.
10. An electronic grade high-purity TiO2 powder prepared by the preparation method according to any one of claims 1 to 9.